2010
DOI: 10.1074/jbc.m109.079822
|View full text |Cite
|
Sign up to set email alerts
|

Wnt2 Regulates Progenitor Proliferation in the Developing Ventral Midbrain

Abstract: Wnts are secreted, lipidated proteins that regulate multiple aspects of brain development, including dopaminergic neuron development. In this study, we perform the first purification and signaling analysis of Wnt2 and define the function of Wnt2 in ventral midbrain precursor cultures, as well as in Wnt2-null mice in vivo. We found that purified Wnt2 induces the phosphorylation of both Lrp5/6 and Dvl-2/3, and activates ␤-catenin in SN4741 dopaminergic cells. Moreover, purified Wnt2 increases progenitor prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 40 publications
2
58
1
Order By: Relevance
“…Recent reports have indicated that Wnt/ β-catenin signaling is required for midbrain DA neurogenesis (30,31), but it is not known which of the multiple canonical Wnts expressed in the VM (13)(14)(15) is/are required for DA neurogenesis. In our study we focused on Wnt1 because Wnt1 −/− mice, unlike Wnt2 −/− mice, for instance (16), show a strong sequential midbrain and DA neuron phenotype (18)(19)(20)(21)(22). Because DA neurons are born in the midbrain FP, we first examined the expression of the FP and basal plate (BP) markers, Shh and the Shh-target gene, Foxa2, both of which are required for DA neuron development (31,(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have indicated that Wnt/ β-catenin signaling is required for midbrain DA neurogenesis (30,31), but it is not known which of the multiple canonical Wnts expressed in the VM (13)(14)(15) is/are required for DA neurogenesis. In our study we focused on Wnt1 because Wnt1 −/− mice, unlike Wnt2 −/− mice, for instance (16), show a strong sequential midbrain and DA neuron phenotype (18)(19)(20)(21)(22). Because DA neurons are born in the midbrain FP, we first examined the expression of the FP and basal plate (BP) markers, Shh and the Shh-target gene, Foxa2, both of which are required for DA neuron development (31,(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…These include Wnt1, Wnt2, and Wnt3a, which activate the Wnt/β-catenin pathway (14,16), and Wnt5a, which activates the Wnt/Rac1 pathway in dopaminergic (DA) cells (17). Wnt1-knockout mice show a partial segmental deletion of the midbrain and hindbrain regions (18,19) resulting from multiple sequential defects, including altered Otx2 and Pitx3 expression, reduced progenitor proliferation, and death of midbrain DA neurons (18)(19)(20)(21)(22).…”
Section: ;Wnt5amentioning
confidence: 99%
“…Wnt-1 KO Altered central and peripheral neuronal development during initial axonogenesis [54] Wnt-1 KO Impaired midbrain development [55] Wnt-1 dominant negative Impaired hippocampal neurogenesis and spatial and object recognition memory [56,57] Wnt-1 overexpression Reduced neural differentiation of mESCs (also by treatment with lithium chloride) [58] Wnt-1 KO Increased differentiation into DA neurons in KO mESCs [59] Wnt-2 KO Decreased progenitor proliferation and neurogenesis in the ventral midbrain [60] Wnt-2 overexpression Induced dendritic arborization in hippocampal progenitors [61] Wnt-3 overexpression Increased differentiation of cortical intermediate [43] progenitors Wnt-3 overexpression Induced differentiation through cleavage of RYK in cortical progenitors [62] Wnt-3a KO Loss of the hippocampus [42] Recombinant Wnt-3a Induced GABAergic neuronal differentiation through RYK, reduced oligodendrogenesis [63] Recombinant Wnt-3a Induced differentiation of hESCs [64] Recombinant/purified Wnt-3a…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
“…The next step is immobilized metal affinity chromatography followed by Superdex gel filtration and, finally, heparin cation exchange (affinity) chromatography (Willert, 2008). This protocol with minor modifications has successfully been used to purify WNT-2, WNT-3A, -5A, -7A, -16, D. melanogaster WNTD, and Wingless (Willert, 2008;Sousa et al, 2010). Even though several WNTs could successfully be purified according to the protocol establish by Karl Willert, it should be emphasized that remaining WNTs still resist purification in a biological active form.…”
Section: Lipoglycoproteins As Receptor Ligandsmentioning
confidence: 99%
“…Purification of WNT-2, WNT-3A, and WNT-5A from conditioned medium was described by the Willert group and others (Willert et al, 2003;Schulte et al, 2005;Mikels and Nusse, 2006;Willert, 2008;Sousa et al, 2010). For this purpose, conditioned medium from WNT overexpressing mammalian cells is harvested and fractionated with affinity chromatography using BlueSepharose, which binds rather selectively to WNT proteins.…”
Section: Lipoglycoproteins As Receptor Ligandsmentioning
confidence: 99%